Fuel use and emissions for non road machinery in Denmark 1985- 2020 - Winther, Morten; Nielsen, Ole-Kenneth (Proceedings from the Annual Transport Conference at Aalborg University, 2006)
This paper explains the new Danish 1985-2020 emission inventory for non road machinery. Stock and operational data are from different statistical sources, research institutes, relevant professional bodies and machinery manufacturers. Updated fuel use and emission factors originate from various measurement programmes. Future factors are tailored to the current EU emission legislation. Beyond the basic calculation approach, the emission computations take into account the effects from engine deterioration, transient loads and gasoline evaporation. The major source of NOx and PM emissions are diesel engines. Most of the HC and CO emissions come from gasoline machinery. From 1985 to 2020, the total fuel use and the emissions of HC, NOx and PM decrease by 7, 43, 62 and 87%, respectively, whereas the CO emissions increase by 7%. In the forecast period from 2005-2020, the percentage NOx and PM emission reductions are almost the same as for road traffic. For HC, the reduction percentage is somewhat smaller, whereas for CO the emission development is so poor, that non road machinery ends up being the largest source of emissions by the end of the forecast period. The availability of new non road emission factors is very useful for other European countries, and work should be done to include these data in the European EMEP/CORINAIR guidebook.